Prognostic value of 24‐hour ambulatory blood pressure patterns in diabetes: A 21‐year longitudinal study. Issue 11 (29th June 2022) - Chiriacò, Martina; Sacchetta, Luca; Forotti, Giovanna; Leonetti, Simone; Nesti, Lorenzo; Taddei, Stefano; Natali, Andrea; Solini, Anna; Tricò, Domenico
Abstract: Aims: To establish the long‐term prognostic value of abnormal circadian blood pressure (BP) patterns in diabetes. Materials and Methods: We retrospectively examined a cohort of 349 outpatients with diabetes who were screened for microvascular complications and followed up for 21 years. Dipping, nondipping and reverse‐dipping status were defined based on 24‐hour ambulatory BP monitoring (ABPM) as ≥10% reduction, <10% reduction, and any increase in average nighttime versus daytime systolic BP (SBP), respectively. Results: After 6251 person‐years of follow‐up (median [range] follow‐up 21.0 [1.1‐22.0] years, 52% women, age 57.1 ± 11.9 years, 81.4% type 2 diabetes and 18.6% type 1 diabetes), a total of 136 deaths (39%) occurred. Compared with dippers, the nondippers and reverse dippers showed progressively higher prevalence of chronic kidney disease (CKD), cardiac autonomic neuropathy (CAN) and postural hypotension. Reverse dippers showed a 13.4% (2.5‐year) reduction in mean overall survival and a twofold increased risk of all‐cause mortality after adjustment for traditional risk factors (hazard ratio 2.2 [95% confidence interval 1.3‐3.8]). Each 1% decrease in nighttime versus daytime SBP ratio was independently associated with a 4% reduction in 20‐year mortality risk. Conclusions: In patients with diabetes, reverse dipping is associated with a higher prevalence of CKD and CAN and more than doubled the adjusted risk of all‐cause mortality over a 21‐year observation.